Oscillating supersonic delta wing with straight leading edges - Crasta, Asha; Khan, Sher Afghan (IJCER, 2012)
A Supersonic similitude has been used to obtain stability derivatives in pitch and roll of a delta wing with straight leading edge for the attached shock case. Ghosh’s strip theory is been used in which strips at different span wise locations are independent of each other. This combines with the similitude to give a piston theory which gives the closed form of solution to stability derivatives in pitch and roll. Some of the results obtained have been compared with those of Hui et al ,Ghosh and Lui &Hui. Results have been obtained for supersonic flow of perfect gas over a wide range of Mach numbers, incidences and sweep angles.